The Metaverse in STEM Education: Interactive Assessment with Electronic Circuits and Arduino mediated by Artificial Intelligence - Bedoya-Cano, Óscar; Marín-Marín, José-Antonio; Sánchez-Amate, José-Jesús; López-Belmonte, Jesús (IJERI: International Journal of Educational Research and Innovation, 2025)
Learning theories that are based on practice and experience are enriched by new forms of virtuality, which open up a range of pedagogical possibilities in digital environments mediated by artificial intelligence. These theories highlight the importance of an effective understanding of phenomena through learning evidence, where assessment plays an essential role. In this context, the representation and simulation of processes become highly valuable pedagogical resources, integrated as key elements in classroom exercises. This article describes the development and application of a set of practices focused on electronic circuits using the CoSpaces metaverse educational platform. The proposal is presented as an alternative for practical assessment that explores the potential of virtual environments to promote experiential learning and the acquisition of electronics skills, allowing students to interact with simulated circuits in an immersive way. Finally, various theoretical and practical implications derived from this work are offered.